Water to the last drop (USA: Discovery Channel School, 2003)
Travels to Canada, the United States, Mexico and the Middle East to study the natural history of water and the latest technologies used to make the water we use is safe.
Executive producer, Adrienne Schure ; production manager, Olivia Foster
Narrator: Nancy Calo and Terry MacDonald
Keywords: Water -- Pollution; Environmental health; Water -- Supply